Strategi Pemasaran Sponge Cake Dengan Subtitusi Aron Dan Kacang Bogor Dengan Pemanfaatan Media Sosial Terhadap Minat Pasar - Hanan, Radinka Ravee; Haqieqi, Sallis Bahihaqi; Minantyo, Hari; Nugraha, Kristian Agung (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
Food is one of the basic human needs, so having sufficient, nutritious and safe food is the human right of every Indonesian to create quality human resources to realize the country's development. Food demand is the sum of direct consumption, industrial needs and other needs. Direct consumption is food consumed directly by the public. The aim of this research is to find out marketing strategies sponge cake with substitution of aron and Bogor peanuts with utilization media social towards market interest, this research uses research methods qualitative, method qualitative examine the depth of facts or events, so that they are local and not in the context of generalizing empirical findings as general events. In this research, researchers will carry out and find out the final results on marketing strategies sponge cake substitution of aron and Bogor peanuts with the utilization media social media on market interest, where researchers will also take data and look for respondents to analyze marketing strategies for products sponge cake. Researchers conducted this research in the city of Surabaya located at Ciputra University Surabaya with assistance from google form as a media of analysis in this research. Keywords: sponge cake, marketing strategy, social media, aron flour and Bogor beans flour